PERBEDAAN MOTIVASI BELAJAR SISWA BERJENIS KELAMIN PEREMPUAN DAN LAKI-LAKI SMK SWASTA BANDUNG - Muhammad Putra Dinata Saragi; Rina Suryani (Jurnal Penelitian Bimbingan dan Konseling, 2018)
This Research is triggered by low  of students’ learning motivation. The purpose of This Research are to: 1) describe students’ learning motivation of female gender, 2) describe students’ learning motivation of male gender, and 3) Differences students’ learning motivation of female gender and male gender. This research used a descriptive differencial quantitative method. The population of this research were X, XI, and XII grade of SMK Swasta Bandung 1 & 2 which totally 240 students. The sample of this research were 150 students, that selected by using proportional stratified random sampling technique. In this research, the researcher used scale as the instrument. The result of validity and reliability of students’ learning motivation state that the instrument of this research was valid and reliable. Data were analyzed with descriptive statistics and t-test. The finding of this research are: 1) on avarage students’ learning motivation of female gender are in high category, 2) on avarage students’ learning motivation of male gender are in high category, 3) there were significant differences between students’ learning motivation of female gender and male gender. Keyword : Learning Motivation, Male, Female